Characterization of termite Trinervitermes trinervoides metagenome-derived glycoside hydrolases, the formulation of synergistic core enzyme sets for effective sweet sorghum and corncob saccharification, and their potential industrial applications - Mafa, Mpho Stephen (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2019)
The current study investigated the biochemical properties of endo-glucanase (GH5E), exo-glucanase (GH5D), xylanase (GH5H) and endo-glucanase/xylanase (GH45), derived from the hindgut bacterial symbionts of a termite (Trinervitermes trinervoides) for their potential role in the biotechnology industry. All these enzymes, except GH5D, exhibited activities on cellulosic and xylan-rich polymeric substrates, which only displayed activity on p-nitrophenyl cellobioside. GH5D, GH5E, GH5H and GH45 enzymes retained more than 80% of their activities at pH 5.5 and also retained more than 80% of their activities at 40ÂºC. Furthermore, these enzymes were thermostable at 37ÂºC for 72 hours. GH5E, GH5H and GH45 were generally stable over a range of metal-ion. The kinetic parameters for GH5E were 5.68 mg/ml (KM) and 34.36 U/mg protein (Vmax). GH5D activity did not follow classical Michaelis-Menten kinetics, suggesting product inhibition. GH5H displayed KM values of 5.53, 95.03 and 2.10 mg/ml and Vmax values of 112.36, 144.45 and 180.32 U/mg protein on beechwood xylan, CMC, and xyloglucan, respectively. GH45 displayed a KM of 6.94 mg/ml and a Vmax of 12.30 U/mg protein on CMC. GH5D [cellobiohydrolase (CBH)] and a commercial CBHII (GH6) enzyme outperformed a commercial CBHI (GH7) enzyme when these enzymes hydrolysed Î²-glucan. GH5D and CBHII also displayed a higher degree of synergy on Î²-glucan but failed to show synergy on Avicel. We therefore concluded that GH5D and CBHII are Î²-glucan-specific cellobiohydrolases. The corncob (CC) and sweet sorghum bagasse (SSB) substrates were pretreated with lime, NaOH and NaClO2. Subsequent to pretreatment, these substrates were used to investigate if GH5D, GH5E, GH5H and GH45 could operate in synergy. Results revealed that out of 12 possible core enzyme sets constructed, only two (referred to as CES-E and CES-H) displayed higher activities on pretreated CC or SSB. Simultaneous synergy was generally the most effective mode of synergy during hydrolysis of alkaline pretreated SSB and CC samples by both CES-E and CES-H. Both core enzyme sets did not display synergy on oxidative pretreated substrates. These findings suggest that lime and NaOH are more effective pretreatments for CC and SSB substrates. We used PRotein Interactive MOdeling (PRIMO) software to demonstrate that GH5D protein structure is an (Î±/Î²)8 barrel with a tunnel-like active site. Enzymes with this type of protein structure are able to perform transglycosylation, a process in which GH5D produced methyl, ethyl and propyl cellobiosides. We concluded that the GH5D, GH5E, GH5H and GH45 enzymes possess novel biochemical properties and that they form synergy during the hydrolysis of complex substrates (SSB and CC). GH5D transglycosylation could be used to produce novel biodegradable chemicals with special properties (e.g. anti-microbial properties). In conclusion, our findings suggest that GH5D, GH5E, GH5H and GH45 can potentially be used to improve biorefinery processes.
Keywords: Termites; Metagenomics; Glucosides; Hydrolases; Enzymes; Feedstock